Unveiling post-COVID-19 dynamics: a comprehensive analysis of customer satisfaction and app usage at Prime Bank's Jatrabari branch - Basir, Abdus Samiul (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.